2013
DOI: 10.1007/s10457-013-9651-8
|View full text |Cite
|
Sign up to set email alerts
|

Crop production under different rainfall and management conditions in agroforestry parkland systems in Burkina Faso: observations and simulation with WaNuLCAS model

Abstract: Traditional agroforestry parkland systems in Burkina Faso are under threat due to human pressure and climate variability and change, requiring a better understanding for planning of adaptation. Field experiments were conducted in three climatic zones to assess Sorghum bicolor (L.) Moench (Sorghum) biomass, grain yield and harvest index in parklands under different rainfall pattern and compared to simulations of sorghum biomass and grain yield with the Water, Nutrient and Light Capture in Agroforestry Systems (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
(65 reference statements)
2
20
0
Order By: Relevance
“…In accordance with previous studies [41,57,69,70], the range of the GOF statistics and the high correlation between the simulated and observed growth parameters for both the calibration (Figure 3) and the validation (Table 4) are indicative of the ability of the WaNuLCAS model to reproduce the early growth dynamics of the tested afforestation species with an acceptable accuracy and precision. A R 2 value of 0.5, CD value of 0.5-2, and EF value above 0.5 represent a good predicted-to-observed relationship [69].…”
Section: Model Performancesupporting
confidence: 89%
See 2 more Smart Citations
“…In accordance with previous studies [41,57,69,70], the range of the GOF statistics and the high correlation between the simulated and observed growth parameters for both the calibration (Figure 3) and the validation (Table 4) are indicative of the ability of the WaNuLCAS model to reproduce the early growth dynamics of the tested afforestation species with an acceptable accuracy and precision. A R 2 value of 0.5, CD value of 0.5-2, and EF value above 0.5 represent a good predicted-to-observed relationship [69].…”
Section: Model Performancesupporting
confidence: 89%
“…The relative increase in AGB, induced by the deep rooting depth, was greater under severe water stress compared to mild water stress, suggesting that deep-rooted saplings are less sensitive to extreme drought than shallow-rooted saplings. Similarly, Coulibaly et al [41] has reported that tree species with deep rooting systems are less vulnerable to water deficits. These results can be attributed to the fact that during extreme drought conditions, deep rooted saplings take advantage of their access to deeper soil horizons, which could result in increased photosynthetic activity and continued biomass production, as reported by Hartl-Meier et al [22] for beech (Fagus sylvatica L.) and larch (Larix decidua Mill.)…”
Section: Effects Of Rooting Depth On Biomass Growth Under Extreme Drymentioning
confidence: 92%
See 1 more Smart Citation
“…Achieving this goal will, however, require extensive understanding of agro-ecological interrelationships and intensive efforts to transfer this knowledge to farmers. 13 See, for example, models by Coulibaly et al (2014) Knoke et al (2014) compared three restoration pathways -afforestation, repasturization with low-input management and high-input management -for a tropical mountain region using 23 ecological, economic and social indicators. Among these options, afforestation showed the highest and low-input pasture management the lowest increase in the socioeconomic and ecological value of these abandoned farmlands.…”
Section: Productive Restoration Of Abandoned and Degraded Landsmentioning
confidence: 99%
“…Their interactions with crops involve complex management decisions in order to maximize total farm level benefits. Regardless of established ecological and provisioning contribution of trees (Bayala et al, 2002), their direct contribution to increased crop yield is often contested (Coulibaly et al, 2014) and context specific (Brandt et al, 2012). For example, on-farm trees and crops compete for resources such as soil moisture and nutrients depending on soil type, climate and tree-crop management (Huth et al, 2010).…”
Section: Introductionmentioning
confidence: 99%